Effects of model essays on the improvement of Iranian IELTS candidates' writing ability - Jafary, Mohamadreza (2014)
There are a number of studies on the efficacy of the common practice of most writing teachers in providing feedback to their students each having their own limitations or flaws. The present study, however, seeking to find some evidence on the effectiveness of providing students with corrective feedback moved one step forward by using a quasi-experimental approach and a qualitative study to provide a better understanding of how the model essay approach is more effective than reformulation as common tradition of writing instruction. Having been pretested for their English knowledge and their writing ability,60 Iranian students were assigned into treatment groups (30) and control groups (30) in two different institutes in Tehran. The treatment group was provided with 10 model essays written by native speakers of English and were instructed to use them as corrective feedback. On the last session all participants were post-tested for their writing ability on IELTS academic writing Task 1and Task 2 (descriptive and argumentative essays) but the treatment group was also interviewed for their experience on the analysis of the model essays and the prominent components which attracted them most when comparing their own works with the model essays they were provided with. In addition to this, their produced LRES (Language related episodes) were counted on four major categories defined by the IELTS academic writing rubric and their level of noticing was operationalized based on the counted LREs and text analysis. The control group had the same hours of instruction practicing how to write first the separate parts of and then whole essays paying attention to the main components identified by IELTS task 1 and 2 writing band descriptor (‘task response,’ ‘coherence and cohesion,’ ‘lexical resource,’ and ‘grammatical range and accuracy’).Intead of model essays participants in the control group used reformulated text as a written feedback. The pre- and post-test writings of all participants were typewritten observing all the misspelling, punctuation errors, grammatical deviations,and use and usage problems in the original hand written copies before being given to 2 independent raters who scored them once for a total score and a second time to determine the sub-scores for the four essay components. The gain scores of the two groups were compared using a two way repeated measure ANOVA followed by post hoc test (Bonferroni) and the results revealed why such patterns in the data and the statistical analysis were observed for the five scores. The treatment group was found significantly better for their total scores and for their sub-scores on the two components of task response, and lexical resources. The result of multi- mediator analysis indicated that the treatment positively affects all 4 sub-scales of IELTS writing rubric but only grammar and lexical resources significantly influenced the IELTS score. This, interestingly, matched with their interviews and produced LREs in the qualitative section of the research. Using model essays as a form of feedback in writing instruction actually improves learners’ writing ability in both IELT academic writing task 1 and 2.